(untitled) (Jurnal Adabiya, 2020)
Evaluation of library collections is a mandatory activity that must be done librarian to keep the quality of collection and existence of the library. The purpose of this study is to explain the efforts made librarians in fulfilling the needs of userinformation through collection evaluation in library with ALA standar. This research uses descriptive qualitative approach using literature study. The results showed that evaluation of library collection can be done with two methods. First, centralized method on a collection; by checking lists, bibliographies, and catalogs, expert opinions (subject specialist), and comparisons of statistical data. Second, the comparison method with various collection standards; by analyzing circulation studies, user opinions, analysis of library borrowing between libraries, citation studies, on-site usage studies (reading room), and availability of shelf collections. Librarians must evaluate collections periodically to keep the collection quality as user needs.